BUDAYA PESANTREN DAN PENDIDIKAN KARAKTER PADA PESANTREN SALAF: (Studi Kausus di Pondok Pesantren Al Munawwar arnujiyyahTasikmalaya) - Mumu (Program Studi Pendidikan Agama Islam, 2025)
The purpose of this study is basically to find out the culture or culture of Islamic boarding schools and character education at the Salaf Islamic boarding school, Al-Munawwar Zarnujiyyah Tasikmalaya, precisely in Kampung Pasirbokor RT 05/01 Kelurahan Cipawitra Kecamatan Mangkubumi Kota Tasikmalaya. The research method used in this study is the descriptive method. The types of data in this study consist of primary data, and secondary data collected and processed by the researcher himself through the interview method. Islamic boarding schools are one of the unique institutions with very strong and inherent characteristics. The role taken is the efforts to educate the nation that have been passed down from generation to generation without stopping. Al Munawwar Zarnujiyyah Islamic Boarding School has a culture in forming character and discipline that has been made in special rules as a habit in everyday life. One example of the culture of students at Al Munawwar Zarnujiyyah Islamic Boarding School is the culture of togetherness, the culture of queuing, the culture of mutual cooperation and other activities. The results of this study indicate: first, Al Munawwar Zarnujiyyah Islamic Boarding School has a strong role in implementing Islamic boarding school culture where the leadership of the Islamic boarding school has made rules and regulations in the form of SOP (Standard Operating Procedures), daily, weekly and monthly schedules. Second, the role of Islamic boarding schools in Supporting the Success of Character Education of students in the Al Munawwar Zarnujiyyah Tasikmalaya Islamic Boarding School environment is carried out by transforming Islamic religious values ​​through the process of instilling habits.